2004
DOI: 10.1245/aso.2004.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Focused Microwave Phased Array Thermotherapy for Ablation of Early-Stage Breast Cancer: Results of Thermal Dose Escalation

Abstract: Thermotherapy causes tumor necrosis and can be performed safely with minimal morbidity. The degree of tumor necrosis is a function of the thermal dose. Future studies will evaluate the impact of high doses of thermotherapy on margin status and complete tumor ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 31 publications
1
54
2
1
Order By: Relevance
“…With this method, the tumor necrosis is often heterogeneous, and early studies have indicated low success rates for complete ablation at 0%-8%. 18,19 In a more recent clinical trial, this technique showed promise in reducing positive margins at excision and a statistically significant decrease in the size of tumors when combined with neoadjuvant chemotherapy. 20 Complications of skin burns and severe pain were observed, and the prone position for a long duration causes more patient discomfort.…”
Section: Microwave Ablationmentioning
confidence: 99%
“…With this method, the tumor necrosis is often heterogeneous, and early studies have indicated low success rates for complete ablation at 0%-8%. 18,19 In a more recent clinical trial, this technique showed promise in reducing positive margins at excision and a statistically significant decrease in the size of tumors when combined with neoadjuvant chemotherapy. 20 Complications of skin burns and severe pain were observed, and the prone position for a long duration causes more patient discomfort.…”
Section: Microwave Ablationmentioning
confidence: 99%
“…Three studies on microwave ablation have been published [23][24][25]. A pilot safety (phase I) study included ten patients with core needle biopsy-proven invasive breast carcinoma (T1-T3 tumors) [23].…”
Section: Microwave Ablationmentioning
confidence: 99%
“…In 68% of the patients, histologic evidence of tumor necrosis was present. Finally, this group published a dose-escalation study [25].…”
Section: Microwave Ablationmentioning
confidence: 99%
“…The dielectric constants and the electrical conductivity of the phantom were adjusted with powdered polyethylene and sodium chloride, respectively, to be equivalent of those in real muscle. The size of the phantom was 190×190×(50 or 60) mm 3 . The thickness of the phantom was small compared to that in Ch.…”
Section: Experimental Devices and Setupmentioning
confidence: 99%
“…Hyperthermia using a lower frequency of microwave (e.g., 433 MHz) has been already studied (2) , but it was not combined with phase control. Phase control techniques were demonstrated at 2.45 GHz (3) , but at that frequency, the depth of penetration is too small to be adequate. Our proposal includes the selection of a suitable frequency in the lower microwave region.…”
Section: Introductionmentioning
confidence: 99%